BUDGETING AS A COMPONENT OF THE COST MANAGEMENT SYSTEM - CHUMAK, Ganna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the article is to generalize the theoretical provisions and methodological principles of cost management at the enterprise when implementing elements of budgeting as a management technology with the aim of making effective management decisions. The relevance of the development and implementation of budgeting is explained by the fact that the economic activity of any enterprise involves the regulation of the volumes of various types of expenses. The efficiency of the enterprise largely depends on the correctly chosen management strategy, the economic potential possessed by the enterprise, on the competitiveness of its products, including the level of costs.It is shown that one of the mechanisms of effective cost management is the budgeting mechanism. Budgeting is the process of planning the future operations of the enterprise and recording its results in the form of a system of budgets. "Budgeting" is also considered as a management technology designed for the development of a financial plan (budget) with the aim of more rational use of resources and increasing the efficiency of management decisions made at the enterprise. The essence of budgeting, as a component of the expenditure management system, consists in the development of interdependent plans for the production, financial and economic activity of the enterprise as a whole and separately for its structural subdivisions, based on current and strategic goals of operation. The role and place of budgeting in the enterprise management system are quite fully characterized by the functions of the budget. It is shown that budgeting ensures the systematic management of the enterprise.It was determined that the problems of methodological principles of management accounting of production costs in the information support of budgeting, not only at the enterprise level, but also, as required by modern conditions of in-depth control, in terms of structural production units of "responsibility centers", can be solved with the use of "flexible" budgets , which are formed during the production process. Management by responsibility centers is one of the subsystems that ensure internal company management.
Keywords: budgeting; enterprise cost management system; enterprise costs; budgeting process; management methods; budget